Fine-Tuning of mTOR mRNA and Nucleolin Complexes by SMN - Francesca Gabanella; Christian Barbato; Marco Fiore; Carla Petrella; Marco de Vincentiis; Antonio Greco; Antonio Minni; Nicoletta Corbi; Claudio Passananti; Maria Grazia Di Certo (Cells, 2021)
Increasing evidence points to the Survival Motor Neuron (SMN) protein as a key determinant of translation pathway. Besides its role in RNA processing and sorting, several works support a critical implication of SMN in ribosome biogenesis. We previously showed that SMN binds ribosomal proteins (RPs) as well as their encoding transcripts, ensuring an appropriate level of locally synthesized RPs. SMN impacts the translation machinery in both neural and non-neural cells, in agreement with the concept that SMN is an essential protein in all cell types. Here, we further assessed the relationship between SMN and translation-related factors in immortalized human fibroblasts. We focused on SMN-nucleolin interaction, keeping in mind that nucleolin is an RNA-binding protein, highly abundant within the nucleolus, that exhibits a central role in ribosomes production. Nucleolin may also affects translation network by binding the mammalian target of rapamycin (mTOR) mRNA and promoting its local synthesis. In this regard, for the first time we provided evidence that SMN protein itself associates with mTOR transcript. Collectively, we found that: (1) SMN coexists with nucleolin–mTOR mRNA complexes at subcellular level; (2) SMN deficiency impairs nucleolar compartmentalization of nucleolin, and (3) this event correlates with the nuclear retention of mTOR mRNA. These findings suggest that SMN may regulate not only structural components of translation machinery, but also their upstream regulating factors.